Increasing Early Childhood Learning Motivation Through Reward Learning Methods at RQ Kaffah Padangsidimpuan - Simbolon, Siti Ena Aisyah; Siti Eni Aisyah Simbolon (Journal of Public Policy Analys, 2023)
Giving gifts to students does not always have a positive impact, but sometimes it can have a negative effect on students. In addition, giving gifts is also not always for children who excel, but sometimes children who are less capable or mediocre but also try to improve their achievements also need to be given gifts to motivate these children. This research is a qualitative approach. Using data sources with documentation and interviews with educators. The results of the interview show that during the learning process educators use the reward method to foster student motivation. The reward method is in the form of words and goods. Educators need attention to the time of giving, the form of reward and the achievement of students when giving rewards. Supporting this, recognizing the character and personality of students needs to be done by educators.